PENGALAMAN KELUARGA (CAREGIVER) MERAWAT PASIEN PASCA STROKE DENGAN GANGGUAN KOMUNIKASI - Salsa Destri Yolanda; Wasisto Utomo; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Stroke is a common neurological disease and should be treat appropriately. Stroke sufferers will appear some problems, one of the problem is communication disorder. Communication disorder will interfere with daily activities so that the patient's family needs help to fulfill daily needs. This research was qualitative research with phenomenological approach that aimed to explore the experience of families caring for patients with communication disorder in post stroke in the area of Puskesmas Harapan Raya. The number of participants in this research are three people taken with purposive sampling technique. Data was collected through semi-structured interviews in the category in-depthinterview. Technique of data analysis with the method of Colaizzi. The research results obtained 5 themes, namely: (1) the description of the patient, (2) the fulfillment of needs, (3) obstacles in caring, (4) impact on families, (5) family response. All of participans knew the characterize of post stroke patient with communication disorder and also take part in fulfill patient daily living. During take care of patient, participants have difficulties especially in daily communication. The impact to family to take care of post stroke patient with communication disorder like physical impact (weigh loss, dizzy, and fatigue), psychologis (sad, bored, and angry), and social (social activity changing). During take care of post stroke patient with communication disorder also have family respons that is positive respon and negative respon that feel by caregivers.The results of this research was expected to be able to obtain a better understanding to families who care for patients with communication disorder in post stroke. This research is recommended for nurses to give health education about how to treat post stroke patient with communication disorder.Keywords: caregiver, communication disorder, experience, stroke